Global warming : rethinking international relations - Chong, Alan (2021)
Recent escalations in the severity of extreme weather events in Europe have set the stage for a rethink of international relations as a policy pathway towards dealing with climate change. Such rethinking requires a refocus on the social contract undergirding sovereignty. Global warming attests to that.